Salivary cytokine levels in early gingival inflammation - Belstrøm D; Damgaard C; Könönen E; Gürsoy M; Holmstrup P; Gürsoy UK. (My University, 2022)
Salivary protein levels have been studied in periodontitis. However, there is lack of information on salivary cytokine levels in early gingival inflammation. The aim of this study was to determine salivary levels of vascular endothelial growth factor (VEGF), interleukin (IL)-8, monocyte chemoattractant protein (MCP)-1, IL-1β, and IL-1 receptor antagonist (IL-1Ra) in gingival inflammation. Twenty-eight systemically and orally healthy nonsmokers abstained from oral hygiene protocols for 10 days. After that, self-performed cleaning was resumed for 14 days. Plaque and gingival indexes were measured, and saliva samples were collected at days 1, 4, 7, 10, and 24. Salivary cytokines were detected with Luminex®-xMAP™. Salivary IL-1β, IL-1Ra, and VEGF levels decreased after 10 days’ development of experimental gingivitis and reached baseline levels at the end of the 2-week resolution period. Salivary IL-8 levels decreased and remained low during development and resolution of experimental gingivitis. Initial inflammation in gingival tissues is associated with a decrease in inflammatory cytokines in saliva. Further studies are needed to evaluate if inflammatory cytokines bind to their functional receptors within the gingival tissue during early gingivitis, which may limits their spillover to the gingival crevice and ultimately saliva.